Impact of Second-Hand Smoke Exposure with Hypertension Status Among Housewives Aged 40-55 Years at Rural Areas - RA Nugraha (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Introduction. As the leading environmental risk factor for cardiovascular diseases, national .....